Sport-specific and non-specific practice of strong and weak responders in junior and senior elite athletics - A matched-pairs analysis - Güllich, A. (Journal of Sports Sciences, 2019)
Elite track and field athletes with greater and lesser multi-year performance improvement were compared regarding their developmental sport-specific and non-specific, organised (coach-led) and non-organised (peer-led) sporting activities. Athlete pairs were matched on gender, discipline and baseline performance in competitions (at 13/19 years). Their unequal subsequent performance development during junior (13-17 years; n = 138) and senior (19-23+ years; n = 80) age ranges defined "strong responders" and "weak responders". Analyses revealed that junior-age strong responders accumulated more organised practice in athletics than weak responders, while the amounts of all other types of activities were indifferent. Senior-age strong responders did not accumulate a greater total sum of all kinds of sport activities or greater amounts of organised practice in athletics or non-organised involvement in athletics or other sports than weak responders. But they engaged in more organised practice and competitions in other sports over more years (9 vs. 2 years) and specialised in athletics at a later age than weak responders (16 vs. 11 years). The results were also robust among senior international medallists vs. national medallists. The findings are reflected relative to the hypotheses of "multiple sampling and functional matching", "learning transfer as preparation for future learning" and "authenticity of variable learning experiences".